Massive Neutrinos: Phenomenological and Cosmological Consequences - Gonzalez, Yuber Ferney Perez (2017)
The XX century witnessed the quantum and relativistic revolutions in physics. The development of these two theories, namely, Quantum Mechanics and Relativity, was the inception of many crucial discoveries and technological advances. Among them, one stands out due to its uniqueness, the neutrino discovery. However, several neutrino properties are still obscure. Neutrinos are the only fundamental particles whose nature is currently unknown. Such fermions can either be different from their antiparticles, i.e., Dirac fermions, or be their own antiparticles, that is, Majorana fermions. On the other hand, the smallness of neutrino masses is a problem seemingly related to the neutrino nature; thus, as essential task consists in addressing the phenomenologically viable models in both cases. Furthermore, it is important to search for other physical process in which the neutrino nature may manifest through different experimental signatures. A rather difficult but promising method corresponds to the detection of the cosmic neutrino background, viz. neutrinos which are relics from the Big Bang. Previous works have shown that detection rates for Dirac and Majorana neutrinos can give different results. Nevertheless, this distinction was obtained considering the Standard Model framework only. Therefore, it is important to understand the consequences of having Non-Standard Interactions contributing to the detection of neutrinos from the cosmic background. Another remarkable relic predicted by Cosmology is the unidentified Dark Matter, composing ~25% of the Universe. All searches regarding the Weakly Interacting Massive Particle, one of the principal candidates for Dark Matter, have given negative results; this has compelled experiments to increase their sensitivity. Notwithstanding, neutrinos may stand in the way of such experimental searches given that they may constitute an irreducible background. In this thesis, we will address these three different phenomena, neutrino mass models, detection of the cosmic neutrino background and the neutrino background in Dark Matter searches, by considering the different characteristics in each case. In the study of neutrino mass models, we will consider models for both Majorana and Dirac neutrinos; specifically, we will probe the neutrinophilic two-Higgs-doublet model. Regarding the detection of relic neutrinos, we will analyse the consequences of the existence of the beyond Standard Model physics in the capture rate by tritium. Finally, we will scrutinize the impact of neutrinos in Direct Detection WIMP searches, by considering Standard Model plus additional interactions in the form of simplified models.